Breastfeeding practices in mothers: a qualitative study - Marzuki, Nanis S.; Yohmi, Elizabeth; Nainggolan, Eveline; Hegar, Badriul; Oswari, Hanifah; Partiwi, I Gusti Ayu Nyoman (Paediatrica Indonesiana, 2014)
Background Despite the WHO and UNICEF recorrunendations,Â the well-known breastfeeding benefits, and the efforts to promote andÂ support breastfeeding; exclusive breastfeeding by Indonesian mothersÂ remains low and contributes to high infant mortality rates. Objective To elucidate the fac tors that influence mothers’ choicesÂ for infant feeding Methods This qualitative study was conducted as part of a nationwideÂ survey. The study included 36 in-depth interviews of mothersÂ with infants aged 0-11 months, and health care professionals,Â including general practitioners, pediatricians, and midwives. ThisÂ study was performed between 0 cto ber - November 2 0 l 0 in bothÂ rural and urban areas of 4 provinces in Indon esia. Results We found that most mothers intended to breastfeedÂ and had positive perceptions of breastfeeding. However,Â mothers faced many challenges in the practice of exclusive andÂ proper breastfeeding. Additionally, the perceived definition ofÂ exclusive breastfeeding varied among the participants, leadingÂ to n on-exclusive breastfeeding attitudes. The most frequentÂ reasons for mothers to introduce additional milk formula orÂ food were the perception of an inadequate milk supply, infantÂ dissatisfaction or fu ssiness after feeding. Different perceptionsÂ were also demonstrated in different regions and the varyingÂ levels of socioeconomic status. Health care practitioners (HCPs)Â were the most reliable source for giving adequate information,Â but unfortunately, they were not easily accessible and providedÂ inconsistent information. Consequently, closely-related familyÂ members were the major contributors of information to a mother’s choice of infant feeding; because they were easily accessible. Conclusion Factors influencing mothers in their breastfeedingÂ practices are their basic knowledge, demographic and socioeconomicÂ status, as well as the availability of support from closelyrelated family members, friends, and HCPs.